Iniciativa para a sustentabilidade do cimento, capacidades dinâmicas verdes e o desempenho de inovação verde - Ribeiro, Olívia Carolina de Resende (2019)
This paper aimed to understand the influence of the adhesion of a Sustainable Initiative on Green Innovation Performance based on Green Dynamic Capabilities in cement industries in Brazil. The thesis is supported by the proposal to adopt Sustainable Initiatives as a factor that influences ex post facto Green Dynamic Capabilities and Green Dynamic Capabilities that influence Green Innovation Performance. To achieve this objective, we used the Cement Sustainability Initiative as a case study. The scope of the research focused on both signatory and nonsignatory Brazilian cement companies. The study was conducted through quantitative and qualitative research procedures. The sample of the quantitative study consisted of 90 questionnaires applied to industry to identify the influence of the ex post facto initiative on Green Dynamic Capabilities and Green Innovation Performance. The qualitative study was conducted based on semi-structured interviews with three managers of the cement industry with over 16 years in the segment. The intent was to absorb the perception of the change, deepening and evaluating the results learned in the quantitative study. We sought to understand whether the relationship between the Cement Sustainability Initiative and the Green Dynamic Capabilities presented feedback, e.i. if it was recursive over time. Considering the case under study, we suggest that the relationship between Green Dynamic Capabilities and the Cement Sustainability Initiative feeds back and are recursive over time.